2022
DOI: 10.1029/2021jg006629
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Soil Gross N2O Emission Driven by Substrates Rather Than Denitrification Gene Abundance in Cropland Agroforestry and Monoculture

Abstract: Conversion of monoculture to agroforestry (integrating trees with crops) is promoted as a promising management in reducing N2O emissions from croplands. How agroforestry influences gross N2O emission (N2O + N2 from N2O reduction) and uptake (N2O reduced to N2) compared to monoculture is unknown. We used the 15N2O pool dilution technique to quantify these processes using soil cores (top 5 cm) incubated in the field with monthly measurements over two growing seasons (2018–2019) at two sites (each with paired agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 67 publications
4
20
0
Order By: Relevance
“…The authors reported an increase from 52 to 81 in MBC and 31 to 63% in MBN in the tree rows as compared to multiple distances in the crop rows [ 39 ]. Three years later, Luo and coworkers verified these findings [ 45 ]. At two sites, the authors were able to show a gradual increase in MBC from the middle of the crop rows (365 mg kg −1 ) to the tree rows (572 mg kg −1 ) [ 45 ].…”
Section: Trees In Agroforestry Systems Increase Soil Microbial Popula...mentioning
confidence: 80%
See 4 more Smart Citations
“…The authors reported an increase from 52 to 81 in MBC and 31 to 63% in MBN in the tree rows as compared to multiple distances in the crop rows [ 39 ]. Three years later, Luo and coworkers verified these findings [ 45 ]. At two sites, the authors were able to show a gradual increase in MBC from the middle of the crop rows (365 mg kg −1 ) to the tree rows (572 mg kg −1 ) [ 45 ].…”
Section: Trees In Agroforestry Systems Increase Soil Microbial Popula...mentioning
confidence: 80%
“…Three years later, Luo and coworkers verified these findings [ 45 ]. At two sites, the authors were able to show a gradual increase in MBC from the middle of the crop rows (365 mg kg −1 ) to the tree rows (572 mg kg −1 ) [ 45 ]. Similarly, MBN was 46 to 69% greater in the tree rows than in the middle of the crop rows [ 45 ].…”
Section: Trees In Agroforestry Systems Increase Soil Microbial Popula...mentioning
confidence: 80%
See 3 more Smart Citations